PENGARUH LEADERSHIP STYLE DAN WORK ENVIRONMENT TERHADAP EFEKTIVITAS KERJA KARYAWAN PADA BAGIAN SEWING DI PT ADIS DIMENSION FOOTWEAR TANGERANG - Indriyani, Nindi; Haki, Ubay (LP2M Universitas Bina Bangsa, 2024)
This study aims to examine and examine the influence of leadership style and work environment either partially or simultaneously on the effectiveness of the sewing department employees at PT Adis Dimension Footwear. Data was taken using a questionnaire to 50 respondents as a sample and primary data sources. There are two independent variables in this research data, namely leadership style (X1) and work environment (X2) and work effectiveness (Y) as the dependent variable. This research uses quantitative research methods with associative methods. Data were analyzed using multiple linear regression using SPSS software version 26.0. The results of the hypothesis test show that the t value of the leadership style variable (-0.085) < t table (2.011) with a significant value of 0.933 > 0.05 so that Ha is rejected, and the t value of the work environment variable (5.021) > t table (2.011) with a significant value of 0.000 < 0.05 so that Ha is accepted, simultaneously the calculated F value of the two independent variables is (71.767) > F table (3.195) with a significance of 0.000 < 0.05 so that Ha is accepted and Ho is rejected. The research findings show that partially the leadership style variable has no significant effect on work effectiveness, while the work environment variable has a significant effect on work effectiveness, simultaneously between leadership style and work environment have a joint effect on work effectiveness